Visualizing Personal Branding: A Multimodal Analysis of 'Flexing' in Instagram - Christanta Rejuna Phanes S Brahmana; Dwi Kurnia Surya Ningrum; Alemina Br. Perangin-angin (Institut Agama Islam Negeri Palopo, 2023)
This study delves into the dynamic phenomenon of